limx→0 xtan⁡2x−2xtan⁡x(1−cos⁡2x)2, is

limx0xtan2x2xtanx(1cos2x)2, is

  1. A

    2

  2. B

    -2

  3. C

    12

  4. D

    -12

    Register to Get Free Mock Test and Study Material

    +91

    Verify OTP Code (required)

    I agree to the terms and conditions and privacy policy.

    Solution:

    limx0xtan2x2xtanx(1cos2x)2

    =limx0x(tan2x2tanx)(1cos2x)2=limx02xtan3x1tan2x(1cos2x)2=limx02tanxx31tan2x1cos2xx22=2×13(10)×4=12

    Chat on WhatsApp Call Infinity Learn

      Register to Get Free Mock Test and Study Material

      +91

      Verify OTP Code (required)

      I agree to the terms and conditions and privacy policy.